Multidimensional Scaling Analysis of Certified Extension Rice Seed Production within the Framework of Sustainable Agriculture - Safira Candra Jalaweni; Amin Setyo Leksono; Anthon Efani; Maharani Pertiwi Koentjoro (Pusbindiklatren Bappenas, 2025)
The production of certified extension rice seed is essential for ensuring the availability of superior and adaptive varieties, yet its sustainability faces cross-dimensional pressures. This study aims to assess the sustainability status of the extension seed production system in West Lombok Regency. Data were collected from rice seed producers using the Slovin formula and verified through cross-checking for accuracy and consistency. The sustainability status was analyzed using Multidimensional Scaling (MDS) based on the RAPHYTON approach. Model validity was confirmed via Monte Carlo simulation, low stress (<0.11), and high R-squared (>0.98). The results indicate a multidimensional sustainability index of 68.47, categorized as moderately sustainable, with social and technological dimensions scoring highest, and economic and ecological dimensions lowest. The study highlights the fragile transitional phase of the extension seed system and recommends policy strategies focusing on market diversification, strengthening seed growers’ capacity, certification reforms, and digital marketing adoption to enhance resilience, inclusiveness, and adaptability.